Factors influencing school bonding among juvenile offenders – The experience of a systematic review - Márta Miklósi; Karolina Eszter Kovács (International Journal of Educational Research Open)
Background: School attendance and school bonding have protective effects against later criminal behaviour, with young people who are not strongly attached to prosocial individuals and conventional institutions more likely to engage in criminal behaviour. Problems with school bonding reinforce the gradual disengagement of students from school, which, together with other personal, social and contextual variables, contributes to the development of deviant behaviour. Methods: A systematic PRISMA review was conducted using EBSCO Discovery Service Search Engine (using 85 databases during searching) to access studies which investigated the association of school bonding of juvenile offenders with risk of subsequent reoffending and successful reintegration into society, finally 10 studies were reviewed. The PICOS format was used to define inclusion criteria, and the Joanna Briggs Institute (JBI) critical appraisal tool was used to assess the quality of the studies. Results: The research reviewed confirmed our hypothesis that increasing school bonding and engagement can support the reintegration of juvenile offenders into society, particularly through extracurricular activities and mentoring. At the same time, we cannot ignore the study of social influences, because family dynamics, peer relationships and partner relationships have a strong influence on school bonding and consequently on the likelihood of delinquency. Conclusions: Although this review has highlighted important links with school bonding among juvenile offenders, future research on this less researched topic would be worthwhile to better understand the nature of school bonding and the opportunities and good practices to strengthen school bonding, thereby increasing the chances of desistance.